Therapeutic properties of VO(dmpp)2 as assessed by in vitro and in vivo studies in type 2 diabetic GK rats - Domingues, N. (2014)
The bis(1,2-dimethyl-3-hydroxy-4-pyridinonato)oxidovanadium(IV), VO(dmpp)2, has shown anti-diabetic effects by in vitro studies in Wistar (W) rat adipocytes and in vivo in obese Zucker rats. The aim of this work is to confirm the therapeutic properties of VO(dmpp)2 in non-obese type 2 diabetic Goto-Kakizaki (GK) rats. An in vivo study was carried out, treating W and GK rats during 21 days with a daily dose of VO(dmpp)2 (44 μmol/kg). It was shown that VO(dmpp)2 doesn't affect the normal increase of body weight of both W and GK rats, after 8 days of treatment ameliorates glycemia in GK rats (8.4 ± 0.3 vs 10.1 ± 0.2 mM in GK control, P < 0.001) but doesn't interfere with glucose levels in W rats and, after 21 days of treatment, improves the glucose intolerant profile of GK rats (13.1 ± 0.5 vs 20.6 ± 0.7 mM/min in GK control, P < 0.001), despite no increase of plasma insulin levels during glucose tolerance test. Additionally, it was demonstrated that VO(dmpp)2 significantly enhances [3-3H]-glucose uptake by W and GK rat adipocytes (non-toxic concentration of 100 μM: respectively 193 ± 20 and 254 ± 21%, P < 0.001, relative to the basal value) showing an efficacy similar to insulin 1.72 nM and better than the same concentration of BMOV (P < 0.01). Western blotting revealed that in W and GK rats VO(dmpp)2 significantly promotes IRS2 (P < 0.05) and p-AKT expression (P < 0.001 and P < 0.05, respectively, relative to the respective controls) and in GK animals reduces the increase of PTP1β expression (P < 0.001, relative to GK control).